Transcriptome Analysis of Liver Cancer Cell Huh-7 Treated With Metformin - Li, Chun-Qing; Liu, Zhi-Qin; Liu, Sha-Sha; Zhang, Gao-Tao; Jiang, Li; Chen, Chuan; Luo, Du-Qiang (Frontiers in Pharmacology, 2022)
Metformin is a kind of widely used antidiabetic agent, which regulates glucose homeostasis through inhibiting liver glucose production and increasing glucose uptake in muscle. Recent studies suggest that metformin exhibits anticancer properties in a variety of cancers. Although several antitumor mechanisms have been proposed for metformin action, its mode of action in human liver cancer remains not elucidated. In our study we investigated the underlying molecular mechanisms of metformin’s antitumor effect on Huh-7 cells of hepatocellular carcinoma (HCC) in vitro. RNA sequencing (RNA-seq) was performed to explore the effect of metformin on the transcriptome of Huh-7 cells. The results revealed that 4518 genes (with log2 fold change>1 or < -1, p-adjusted value<0.05) were differentially expressed in Huh-7 cells with treatment of 25mM metformin compared to 0mM metformin including 1812 up-regulated and 2706 down-regulated genes. Gene ontology and KEGG pathway analyses identified 54 classical pathways which were significantly enriched, and 16 pathways are closely associated with cancer, such as cell cycle, DNA replication, ECM-receptor interaction and so on. We selected 11 differentially expressed genes, which are closely associated with HCC to validate their differential expressions through quantitative real-time reverse transcription PCR (qRT-PCR). The result exhibited that the genes of FASN, MCM6, MCM5, MARCKS, FADS2, CXCL1, BMP4, SKP2, KNG1, PCNA were down-regulated and DUSP1 is significantly up-regulated in Huh-7 cells with treatment of 25mM metformin. These differentially expressed genes and pathways might play a crucial part in the antitumor effect of metformin, and might be potential targets of metformin treating HCC. Further investigations are required to evaluate the metformin mechanisms of anti-cancer action in vivo.